Detection and activity of MMP-2 and MMP-9 in Leishmania amazonensis and Leishmania braziliensis promastigotes - Brenda Furtado Costa; Tarcísio Navegante de Queiroz Filho; Adeniele Lopes da Cruz Carneiro; Aline Semblano Carreira Falcão; Maria Sueli da Silva Kataoka; João de Jesus Viana Pinheiro; Ana Paula Drummond Rodrigues (BMC Microbiology, 2023)
Abstract Metalloproteinases (MMPs) are remarkable zinc-dependent endopeptidases, critical for degrading components of the extracellular matrix, thus actively influencing cell migration. Their impact on intracellular parasites, such as the enigmatic protozoan Leishmania, elicits intriguing queries. This study explores into the untapped territory of MMP-2 and MMP-9 within Leishmania spp. promastigotes. Notably, we successfully detected and quantified these MMPs, while also evaluating their activity in two distinct Leishmania species—L. amazonensis (La) and L. braziliensis (Lb)—at various growth stages and isolated from distinct clinical tegumentar disease forms. The results unveiled the presence of MMP-2 and MMP-9 in both species, albeit with distinct localization patterns. Specifically, MMP-9 exhibited significantly higher gelatinolytic activity in La when compared to Lb. Moreover, our data cleverly illustrated the presence and release of MMP-2 and MMP-9 by La and Lb promastigotes, exposing their ability to invade and migrate within a collagen matrix. This pioneering study establishes a compelling correlation between MMP-2 and MMP-9 and their potential role in the dynamics of La and Lb infection. Suggesting their potential as prognostic markers for severe leishmaniasis and promising target molecules for therapeutic interventions, this research opens new avenues for combatting this debilitating parasitic disease.